Essentials of human anatomy and physiology - John W Hole (W.C.Brown, 1995)
This book is designed to provide accurate information about the structure and function of the human body in a interesting and readable mannerIt is organized in 5 units: Unit 1 discusses the structure and function of cells and tissues; Unit 2 deals with the skeletal and muscular systems, which support and protect body parts and make movements possible; Unit 3 describes the nervous and endocrine systems which integrate and coordinate body function; Unit 4 discusses the digestive, respirator, circulatory, lymphatic, and urinary systems; Unit 5 describes male and female reproductive systems, their functions in producing offspring and the early growth and development of this offspring